fNIRS vs. EEG in audiological diagnostics: novel approaches to recording brain responses to auditory stimulation - Mimra, Tomas; Augustynek, Martin; Klein, Lukas (Frontiers in Medicine, 2025)
BackgroundElectroencephalography (EEG) is the traditional method for Auditory Evoked Potentials (AEPs) like Brainstem Auditory Evoked Response (BERA), offering excellent temporal resolution but facing limitations in portability and patient comfort. This study investigates functional Near-Infrared Spectroscopy (fNIRS) as a non-invasive, hemodynamic-based alternative.MethodsWe performed simultaneous EEG and fNIRS measurements on healthy volunteers to compare responses to two auditory stimuli: rapid ”clicks” (n = 20) and slower, complex “warbles” (n = 34). Data were analyzed using correlation, t-tests, a General Linear Model (GLM), and Principal Component Analysis (PCA) to assess and compare signal quality and robustness.ResultsFor rapid click stimulation, EEG demonstrated its superiority in detecting millisecond-scale Jewett waves. While fNIRS showed transient features in temporal proximity to auditory brainstem responses (ABRs), it could not resolve these fast potentials. For the slower warble stimulation, fNIRS excelled, detecting significant hemodynamic changes in all participants. A comprehensive analysis, including a repeated-measures Analysis of Spatial Specificity (ANOVA), confirmed a highly structured, repeatable, and spatially specific response, arguing against systemic artifacts and supporting a neural origin.ConclusionEEG remains the indispensable tool for rapid auditory brainstem diagnostics. However, fNIRS shows significant potential for measuring robust cortical responses to slower, more complex auditory stimuli. With advantages in comfort and portability, fNIRS can serve as a valuable complement to EEG, particularly in clinical scenarios where EEG application is constrained, such as in pediatric or mobile audiological assessments.